Human Papilloma Virus and oral cancer: Narrative review of the literature. - Alejandra Fernández; Maureen Marshall; Alfredo Esguep (Universidad de Concepción., 2014)
The Human Papilloma Virus (HPV) infection is now more common sexually transmitted diseases, with an incidence of 5.5 million worldwide, with 85% of the carrier of this virus adult population. Their oncogenic potential and increased oral lesions associated with oral HPV infection have led us to make a narrative of the literature on the role of HPV in oral cancer, especially types 16 and 18. Here we refer to the possible routes of infection, oncogenic mechanisms, both benign and potentially malignant oral lesions associated with the infection, different methods used for detection, prediction and prevention of infection. We stress the importance of the role of the dentist to identify individuals considered high risk and ease of performing detection in the oral cavity, through a quick and easy method as exfoliative cytology.